Microbial Biofilm Voltammetry: Direct Electrochemical Characterization of Catalytic Electrode-Attached Biofilms - Marsili, Enrico; Rollefson, Janet B; Baron, Daniel B; Hozalski, Raymond M; Bond, Daniel R (Applied and Environmental Microbiology, 2008)
While electrochemical characterization of enzymes immobilized on electrodes has become common, there is still a need for reliable quantitative methods for study of electron transfer between living cells and conductive surfaces. This work describes growth of thin (<20 μm) Geobacter sulfurreducens biofilms on polished glassy carbon electrodes, using stirred three-electrode anaerobic bioreactors controlled by potentiostats and nondestructive voltammetry techniques for characterization of viable biofilms. Routine in vivo analysis of electron transfer between bacterial cells and electrodes was performed, providing insight into the main redox-active species participating in electron transfer to electrodes. At low scan rates, cyclic voltammetry revealed catalytic electron transfer between cells and the electrode, similar to what has been observed for pure enzymes attached to electrodes under continuous turnover conditions. Differential pulse voltammetry and electrochemical impedance spectroscopy also revealed features that were consistent with electron transfer being mediated by an adsorbed catalyst. Multiple redox-active species were detected, revealing complexity at the outer surfaces of this bacterium. These techniques provide the basis for cataloging quantifiable, defined electron transfer phenotypes as a function of potential, electrode material, growth phase, and culture conditions and provide a framework for comparisons with other species or communities.